PENGAWETAN LIMA JENIS KAYU DENGAN PROSES SEL PENUH - Barly Barly; Emmy Yetty (Jurnal Penelitian Hasil Hutan, 1989)
Five wood species Shorea hopeifolia Sym; Palaquium ferox H.J.L.; Dillenia eximia Miq; Hopea sangal Kortn.; Tristania maingayi Duthie treated with copper-chrome-arsenic (CCA) preservative, were studied using the full cel process. The treatments comprising concentration, pressure, and pressure period, and the responses are penetration and the retention of preservative.